Experience, Engagement and Trust Effects towards Brand Loyalty - Amelia Saraswati; Erris Dwiki Mahardika; Gian Pradipta Hadisoebrotot; Patrick Armando Jonathan (Fakultas Ekonomi dan Bisnis Universitas Pancasila Jakarta, 2024)
This research adds to the existing correlation by elucidating and substantiating the impact of brand trust on brand loyalty and examining the relationship between brand experience factors towards customer engagement on brand loyalty. Data were gathered via online surveys and a descriptive quantitative design from respondents who had previously purchased fashion brands. To verify the hypotheses, a structured modeling technique was employed. The findings showed a wide range of substantial positive connections between brand experience on consumer engagement and brand loyalty. Brand trust is also influenced by brand loyalty. It is anticipated that it would give management vital data and practical insights into consumers' purchase behavior, which will help clothing companies sustain.